2014
DOI: 10.3109/00365548.2014.907929
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of severe hand, foot and mouth disease: A meta-analysis

Abstract: Duration of fever ≥ 3 days, body temperature ≥ 37.5°C, lethargy, hyperglycemia, vomiting, increased neutrophil count, EV71 infection, and young age are risk factors for severe HFMD. A confirmed diagnosis at first visit to hospital can significantly decrease the risk of severe HFMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 21 publications
7
46
4
Order By: Relevance
“…We found that the absence ulcers or herpes in the mouth and the presence of maculopapular rash were indicators of severe disease, which is consistent with previous studies152122. However, in a recent meta-analysis23, different findings were presented, showing that there may be no association between ulcers in the mouth and the risk of progressing severe complications. Platelet count increase associating with severe HFMD was reported in some studies.…”
Section: Discussionsupporting
confidence: 90%
“…We found that the absence ulcers or herpes in the mouth and the presence of maculopapular rash were indicators of severe disease, which is consistent with previous studies152122. However, in a recent meta-analysis23, different findings were presented, showing that there may be no association between ulcers in the mouth and the risk of progressing severe complications. Platelet count increase associating with severe HFMD was reported in some studies.…”
Section: Discussionsupporting
confidence: 90%
“…As demonstrated, both in our study and other reports282930, the EV-A71 infection accounted for a large proportion in severe cases. It was taken as an independent risk factor in the severity development at all times.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, NS involvement variables, including limb jitters, nystagmus, ataxia, and acute flaccid paralysis, were predictors of treatment failure in severe cases, whereas the variables of a poor spirit, headache and vomiting, convulsions, and signs of irritation, were not significantly different between the efficiency and invalid cases of the S. baicalensis group, which is consistent with previous studies [5, 23, 24]. In addition, the FBG level and PWBC count were shown to influence the effectiveness of S. baicalensis injection, and both have been reported to be significantly increased in patients with severe HFMD [25]. Conversely, CSF-WBC counts and EEG and brain MRI abnormalities did not appear to influence the efficacy of the treatment.…”
Section: Discussionsupporting
confidence: 89%